Konsep Siyasah dalam Yahudi dan Islam - Anshori, Ahmad Yani (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2016)
The  essence  of  siyasah  is  the  management  of  the  umat`s affairs  by  the  government  based  on  akhlak.  Siyasah  held in  certain territory  and  particular  political  contract  anyway.  The  aim  is  to establish the religion and maintain worldly affairs towards the common maslahah.  In  the  discourse  of  history,  the  responses  to  siyasah  are different.  There  are  who  regard  siyasah  as  the  cause  of  Muslim`s stagnation, but the others assert siyasah as the foundation, pillar, and moral  to  regulate  state  and  government.  The  discourse  of  siyasah  in Jews and Islam are the real examples of these responses.